The use of myofunctional appliance on children with tongue thrusting habit: A systematic review - Rafa', Nadiya Fathya; Indriyanti, Ratna; Chemiawan, Eka (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Tongue thrusting is a common parafunctional habit that occurs when the tongue comes into contact with the anterior teeth during swallowing. Myofunctional appliance, or functional appliance, are orthodontic devices that can be used to treat tongue thrusting. This systematic review aims to determine the effectiveness of using myofunctional appliances in children with tongue thrusting habits. Methods: The research procedures for this systematic review followed PRISMA guidelines. Articles were searched using the keywords (myofunctional appliance OR functional appliance) AND (mixed dentition) AND (tongue thrust OR tongue thrusting) in databases including PubMed, ScienceDirect, Scopus, EBSCOhost, and Google Scholar, covering the period from 2013 to 2023. The inclusion criteria were studies discussing the use of myofunctional appliances in children in the mixed dentition stage with tongue thrusting habits. Articles meeting the inclusion criteria were evaluated for quality using the JBI critical appraisal tools. Results: A total of 5 articles meeting the inclusion criteria indicated that myofunctional appliance can eliminate tongue thrusting habits in children by correcting atypical swallowing patterns and improving tongue positioning. Conclusion: Tongue thrusting habits in children can be eliminated using myofunctional appliances. The success of the treatment depends on the child’s compliance and cooperation.KEYWORDS: Myofunctional appliance, functional appliance, tongue thrusting, mixed dentitionPenggunaan alat miofungsional pada anak dengan kebiasaan tongue thrusting: ulasan sistematikABSTRAKPendahuluan: Tongue thrusting adalah kebiasaan parafungsional yang umum terjadi ketika lidah berkontak dengan gigi anterior saat menelan. Alat miofungsional, atau alat fungsional, merupakan salah satu alat ortodonti yang dapat digunakan untuk menangani tongue thrusting. Tujuan tinjauan sistematik ini bertujuan untuk mengetahui efektivitas penggunaan alat miofungsional pada anak dengan kebiasaan tongue thrusting. Metode: Prosedur penelitian dalam tinjauan sistematik ini mengikuti pedoman PRISMA. Pencarian artikel dilakukan dengan memasukkan kata kunci (myofunctional appliance OR functional appliance) AND (mixed dentition) AND (tongue thrust OR tongue thrusting) pada database PubMed, ScienceDirect, Scopus, EBSCOhost, dan Google Scholar dalam rentang waktu 2013-2023. Kriteria inklusi mencakup studi yang membahas penggunaan alat miofungsional pada anak di tahapan mixed dentition yang memiliki kebiasaan tongue thrusting. Artikel yang memenuhi kriteria inklusi dievaluasi kualitasnya menggunakan JBI critical appraisal tools. Hasil: Sebanyak 5 artikel yang memenuhi kriteria inklusi menunjukan bahwa alat miofungsional dapat menghilangkan kebiasaan tongue thrusting pada anak dengan mengoreksi pola menelan yang tidak normal (atypical swallowing) dan memperbaiki posisi lidah. Simpulan: Kebiasaan tongue thrusting pada anak dapat dihilangkan menggunakan alat miofungsional. Keberhasilan perawatan bergantung pada sikap kepatuhan dan kooperatif pada anak.KATA KUNCI: Alat miofungsional, alat fungsional, tongue thrusting, mixed dentition